2004
DOI: 10.1095/biolreprod.103.021345
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Prevents Fasting-Mediated Reductions in Pulsatile Secretion of Luteinizing Hormone and Enhances Its Gonadotropin-Releasing Hormone-Mediated Release in Heifers1

Abstract: We tested the hypothesis that leptin could prevent fasting-mediated reductions in pulsatile secretion and modify GnRH-mediated release of LH in heifers approaching puberty. Thirteen crossbred, prepubertal heifers (13.5-16 mo; 280-350 kg) exhibiting frequencies of pulses of LH between 0.67 and 1 pulse/h, were assigned randomly to two groups: 1). control (n = 6), fasted for 72 h with s.c. injections of saline at 12-h intervals, and 2). leptin (n = 7), fasted for 72 h with s.c. injections of oleptin (19.2 microg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 39 publications
4
23
0
7
Order By: Relevance
“…This agrees with most previous studies of fasted or fooddeprived animals that found reductions in serum leptin; however, they tested periods longer than 24 hr (Ahima et al 1996;Casanueva and Dieguez 1999;Dallman et al 1999;Schneider and Zhou 1999;Schneider et al 2000Schneider et al ,2002Maciel et al 2004;Luque et al 2007). Fasting-mediated reductions in serum leptin after 24 hr …”
Section: Development Of the Short-term Fasting Modelsupporting
confidence: 91%
“…This agrees with most previous studies of fasted or fooddeprived animals that found reductions in serum leptin; however, they tested periods longer than 24 hr (Ahima et al 1996;Casanueva and Dieguez 1999;Dallman et al 1999;Schneider and Zhou 1999;Schneider et al 2000Schneider et al ,2002Maciel et al 2004;Luque et al 2007). Fasting-mediated reductions in serum leptin after 24 hr …”
Section: Development Of the Short-term Fasting Modelsupporting
confidence: 91%
“…This points to independent regulators for pituitary leptin and our studies show that they include estrogen and GHRH [98] and GnRH [93], all of which would be reduced in a fasted state [20,58,67,68,76,78,186,187]. NPY would not be reduced, however receptors for this neuropeptide would likely be reduced because of the requirement for estrogen, at least in female rats.…”
Section: Pituitary Leptin and Paracrine Interac-tionsmentioning
confidence: 58%
“…Moreover, treatment with exogenous leptin prevented these decreases, implying a direct action of leptin at the hypothalamic level (Maciel et al, 2004a). In contrast, mature cows subjected to similar feeding restrictions, resulting in analogous metabolic responses to those seen peripubertal heifers (e.g., decreased leptin mRNA expression in adipose tissue, decreased plasma concentrations of leptin, insulin and IGF-1), did not exhibit a decrease in the pulsatile secretion of LH (Maciel et al, 2004b). However, similar to the heifers, mature cows subjected to short-term fasting became intensely hypersensitive to exogenous leptin.…”
Section: Leptin and Reproductionmentioning
confidence: 90%